2017
DOI: 10.1007/s11739-017-1776-8
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department visits among patients with left ventricular assist devices

Abstract: Continuous-flow left ventricular assist devices (LVADs) are increasingly implanted to support patients with end-stage heart failure. These patients are at high risk for complications, many of which necessitate emergency care. While rehospitalization rates have been described, there is little data regarding emergency department (ED) visits. We hypothesize that ED visits are frequent and often require admission after LVAD implantation. We performed a retrospective review of patients in our health-care system fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
2
18
0
1
Order By: Relevance
“…Broadening this definition to include bleeding and stroke, known complications of continuous-flow LVADs, still accounts for fewer than 1 in 5 LVAD ED presentations. This pattern is similar to that described previously in the literature, and is likely a manifestation of 24-hour care provided by the LVAD team and coordinators at our center and many others, which can facilitate expedited direct admission to LVAD trained units for suspected device-related complications and malfunctions [3] , [4] , [5] . The overall admission rate from the ED in our study is similar to those of prior evaluations, suggesting that the overwhelming majority of LVAD presentations to the ED result in admission [5] , [6] .…”
Section: Discussionsupporting
confidence: 85%
“…Broadening this definition to include bleeding and stroke, known complications of continuous-flow LVADs, still accounts for fewer than 1 in 5 LVAD ED presentations. This pattern is similar to that described previously in the literature, and is likely a manifestation of 24-hour care provided by the LVAD team and coordinators at our center and many others, which can facilitate expedited direct admission to LVAD trained units for suspected device-related complications and malfunctions [3] , [4] , [5] . The overall admission rate from the ED in our study is similar to those of prior evaluations, suggesting that the overwhelming majority of LVAD presentations to the ED result in admission [5] , [6] .…”
Section: Discussionsupporting
confidence: 85%
“…This is congruent with the results of previous studies. 6 , 7 Risk factors for bleeding in this population include anticoagulation, development of arteriovenous malformations, and acquired von Willebrand disease. 2 It is, therefore, extremely important that ED providers be familiar with the workup and management of bleeding complications in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical studies have illustrated the effectiveness and complications of LVADs, 3 , 4 but literature on the emergency department (ED) presentation of this population is limited, particularly with regard to device-specific complications. 5 7 In addition to the complications associated with heart failure, patients with LVADs are at risk for critical adverse events such as intracranial and gastrointestinal bleeding, driveline infection, and pump thrombosis. Early diagnosis of pump thrombosis is critical, as it can result in urgent transplantation, device replacement, or death.…”
Section: Introductionmentioning
confidence: 99%
“…Although the overall current number of US presentations is not known, one major medical center with an affiliated LVAD program performed a retrospective chart review of all patients who had received an LVAD implantation from 2011 to 2015 and found a rate of 3.49 visits per patient during the study period. 2 According to the Centers for Medicare & Medicaid Services, there are 183 facilities offering VAD destination therapy, many of which have associated emergency medicine (EM) residencies. 3 Emergency physicians are now expected to know how to provide initial assessments and interventions for these patients, and it is imperative that they coordinate consultation with the designated ventricular assist device (VAD) management team for both routine and critical presentations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the overall current number of US presentations is not known, one major medical center with an affiliated LVAD program performed a retrospective chart review of all patients who had received an LVAD implantation from 2011 to 2015 and found a rate of 3.49 visits per patient during the study period. 2 According to the Centers for Medicare & Medicaid Services, there are 183 facilities offering VAD destination therapy, many of which have associated emergency medicine (EM) residencies. 3…”
Section: Introductionmentioning
confidence: 99%